Mitochondrial abnormalities as a target of intervention in acute myeloid leukemia - Tjahjono, Elissa; Daneman, Megan R.; Meika, Bernadetta; Revtovich, Alexey V.; Kirienko, Natalia V. (Frontiers in Oncology, 2025)
Acute myeloid leukemia (AML) is an aggressive hematological malignancy; it is the most common acute leukemia in adults. AML prognosis is often poor, and relapse often occurs after initial remission. Recurrent genetic abnormalities underlying this disease and the presence of leukemic stem cells complicate disease treatment. However, the complex metabolic reprogramming that enables the unrestrained cell growth seen in these cells may also be their Achilles’ heel. In these cells, mitophagy operates as a double-edged sword. On one hand, it provides a source of building blocks for further cell division and serves as a method for removing damaged organelles, promoting cell survival. However, the profound metabolic changes to mitochondria also render these organelles more sensitive to damage and place them precariously close to excess mitophagic activation. This review discusses the dual role mitophagy plays in AML survival, the importance of targeting mitophagy to treat AML, and current progress in the area. The discovery and mechanism of action of multiple compounds that were used to inhibit or stimulate mitophagy and their effects on AML survival are also described. Further, we explore the combination strategy of mitophagy-targeting compounds with existing and/or novel chemotherapeutics to eradicate AML and discuss strategies to uncover new drug targets and novel mitochondria-targeting drugs.